Effect of Coulomb diffusion of ions on the pulsational properties of da white dwarfs - Althaus, Leandro Gabriel (2020)
Context. Element difiusion is a key physical process that substantially affects the superficial abundances, internal structure, pulsation properties, and evolution of white dwarfs. Aims. We study the effect of Coulomb separation of ions on the cooling times of evolving white dwarfs, their chemical profiles, the Brunt-Vaisala (buoyancy) frequency, and the pulsational periods at the ZZ Ceti instability strip. Methods. We followed the full evolution of white dwarf models in the range 0:51:3 M derived from their progenitor history on the basis of a time-dependent element difiusion scheme that incorporates the effect of gravitational settling of ions due to Coulomb interactions at high densities. We compared the results for the evolution and pulsation periods of ZZ Ceti stars with the case where this effect is neglected. Results. We find that Coulomb sedimentation profoundly alters the chemical profiles of ultra-massive (M? & 1 M) white dwarfs throughout their evolution, preventing helium from difiusing inward toward the core, and thus leading to much narrower chemical transition zones. As a result, significant changes in the g-mode pulsation periods as high as 15% are expected for ultra-massive ZZ Ceti stars. For lower mass white dwarfs, the effect of Coulomb separation is much less noticeable. It causes period changes in ZZ Ceti stars that are below the period changes that result from uncertainties in progenitor evolution, but larger than the typical uncertainties of the observed periods. Conclusions. Coulomb difiusion of ions profoundly affects the difiusion flux in ultra-massive white dwarfs, driving the gravitational settling of ions with the same A=Z (mass to charge number).We show that it strongly alters the period spectrum of such white dwarfs, which should be taken into account in detailed asteroseismological analyses of ultra-massive ZZ Ceti stars.